Strategi Mengajar Siswa Lamban Belajar (Slow Learners): a Narrative Review - Mei Lina Wati; Wiwin Hendriani (EduInovasi: Journal of Basic Educational Studies, 2024)
Slow learners are students who have a slower learning speed than children in general. Slow learner students have their own characteristics and ways of learning according to their needs. The purpose of this study was to known various teaching strategies for slow learner. This study applied the narrative literature review method which data obtained by searching at site databases journal like Google Scholar and Science Direct. Keywords used in search journal namely “Strategi belajar Slow Learner”, “Siswa Lamban Belajar”, Slow Learner Teaching Strategy”, and “Slow Learner”. Journal found identified and selected based on criteria inclusions that have determined and obtained 4 journals for reviewed. Review results literature explain appropriate learning strategies for slow learner children, namely: 1) modifying learning, starting from the curriculum, subject matter, and evaluation methods according to the needs of slow learner students, 2) determining a learning approach that is oriented to student diversity, 3) selecting a learning model which allows students to be actively involved, think, discover, and learn by experiencing directly, 4) choosing learning methods that are adapted to the characteristics of slow learners , 5) using concrete or visual learning media, 6) providing more guidance through remedial or additional tutoring. Keywords: Teaching Strategy, Slow Learner, Elementary School